DAMPAK PEMBANGUNAN BANDAR UDARA BLIMBINGSARI TERHADAP SEKTOR PARIWISATA DI KABUPATEN BANYUWANGI TAHUN 2011-2017 - Adiputra, Yoga (Historia, 2024)
This study discusses the impact of the development of Blimbingsari Airport on the tourism sector in Banyuwangi Regency from 2011 to 2017. The main problem studied is how the impact of the development of Blimbingsari Airport on the tourism sector in Banyuwangi Regency from 2011 to 2017. The purpose of this study is to explain what it is about which received influence from the development of Blimbingsari Airport. This study uses historical research methods. The results of this study indicate that Banyuwangi's tourism potential can develop with the support of the local government through airport development policies. The number of tourists and the number of passengers at Blimbingsari Airport from 2011-2017 has continued to increase. Many local and foreign tourists visit Banyuwangi to take part in activities in the form of events or enjoy the natural beauty and local arts in Banyuwangi. Foreign tourists, of course, come to Banyuwangi using air transportation. Thus, Blimbingsari Airport can be used as a promotional medium to reach Banyuwangi as an international tourism industry area. Keywords: Blimbingsari airport; economy; Banyuwangi regency; tourism